Composite current collector
By combining polymer materials and thermally deformed sheets in the base film of composite fluid collection, multi-point and large-area quick circuit breaking at high temperatures is achieved, and the poor binding force between metal layer and polymer layer in the prior art is solved. Problem, improving the thermal safety performance and service life of the battery.
Patent Information
- Application Number
- CN202411588915.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing composite liquid collector has poor bonding power to the polymer layer in the electrolyte environment, resulting in metal delamination, cracking and discontinuity, reducing the conductivity of the electrode material, increasing the internal resistance of the battery, and causing safety problems.
Using a composite fluid including a base film, an oxide coating and a conductive layer, the base film combines polymer material and a thermal deformation sheet. The thermal deformation sheet drives the conductive metal layer and oxide coating to form multi-point and large-area through deformation. Quickly open circuit.
It improves the thermal safety performance of the composite fluid collector and battery, optimizes the conductive properties and mechanical strength, extends the service life, and effectively reduces the thermal risk of the battery.
Smart Images

Figure CN119481076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite current collector. Background Art
[0002] The "sandwich structure" of the composite current collector can achieve a "short-circuit effect" and significantly improve thermal stability. When the battery is broken by external impact, almost no metal burrs are generated, which avoids puncturing the battery separator, reduces the risk of battery short circuit, and greatly improves battery safety. In addition, even if the battery causes an internal short circuit due to puncture or other reasons, the short circuit cannot continue due to the fusing effect of the composite current collector, thus avoiding the risk of battery combustion and explosion. However, when the composite film prepared based on this strategy is used as a current collector in lithium-ion batteries, the poor bonding between the metal layer and the polymer layer in the electrolyte environment system will cause more serious metal delamination, cracking of the metal layer, and discontinuity and unevenness. These behaviors will greatly reduce the conductivity of the electrode material and increase the internal resistance of the battery, thereby causing battery safety problems when the battery encounters high temperature and produces thermal effects.
[0003] In view of this, how to further improve the safety performance of the current collector is of great significance for improving battery safety performance and reducing battery thermal risks. Summary of the invention
[0004] In order to solve the problems and deficiencies in the prior art, the present invention provides a composite current collector, which has a different principle from the traditional "sandwich structure" composite current collector to achieve the "short circuit effect". When encountering high temperature, it can quickly break the circuit at multiple locations and over a large area, thereby further improving the thermal safety performance of the composite current collector and the battery. At the same time, the composite current collector in the present invention also has relatively excellent electrical conductivity and mechanical strength, which can further optimize the thermal safety performance of the composite current collector and the battery, and extend the service life of the composite current collector and the battery.
[0005] The present invention provides a composite current collector, which comprises a base film, an oxide coating, and a conductive layer in sequence; the base film comprises a polymer material and a thermal deformation sheet; in the base film, the thermal deformation sheet is completely wrapped by the polymer material; or in the base film, the thermal deformation sheet is combined with the polymer material in an internal and external interlaced manner; the polymer material comprises at least one of polypropylene, polyethylene terephthalate, and polyimide; the thermal deformation sheet comprises at least one of a bimetallic sheet and a memory metal sheet.
[0006] At present, the composite current collector will melt quickly in the event of thermal runaway, forming a "circuit-breaking effect", and the intermediate layer substrate is an insulating layer that can wrap the metal layer, which can effectively prevent the positive and negative electrodes from short-circuiting. For example, during the puncture process, the composite current collector is directly disconnected, avoiding the short-circuit point, thereby improving safety performance. However, the above short circuits are usually point disconnections, which only occur in the failure area, while other areas cannot be cut off in time, and there is still a risk of continued conduction. In addition, the non-conductive nature of the base film itself and the micron-level metal layer make it impossible for the composite current collector to further reduce the square resistance, and the thermal effect during the short circuit is more serious.
[0007] The present invention, from another perspective, combines polymer materials and thermally deformable sheets in a specific way, so that the thermally deformable sheets and polymer materials can be closely combined to form a community, thereby optimizing the conductive properties and mechanical properties of the base film and even the composite current collector as a whole. At the same time, the thermally deformable sheets can be effectively deformed in time at high temperatures, quickly forming a large area short circuit, and improving the thermal safety performance of the composite current collector. Specifically, firstly, the thermally deformable sheet is a thermally deformable metal sheet or a thermally deformable metal alloy sheet, which includes a bimetallic sheet or a memory metal sheet. The bimetallic sheet or the memory metal sheet can be deformed at a certain high temperature. This deformation will bring a relatively large tension to the conductive metal layer on the surface, driving the middle oxide coating (such as a ceramic base layer) with greater brittleness to undergo continuous microcrack fracture, achieving multi-point and large-area rapid circuit breaking, and further improving the thermal safety of the composite current collector. Secondly, the heat-deformed metal sheet or heat-deformed metal alloy sheet forms a metal network in the base film, which can increase the conductivity of the composite current collector, so that during the battery charging and discharging process, the composite current collector can reduce its own overcurrent heating, further reduce thermal risks, and improve the thermal safety performance of the composite current collector and the battery. Thirdly, the introduction of heat-deformed metal sheets or heat-deformed metal alloy sheets can also improve the tensile strength of the base film. This metal network can also serve as a skeleton connecting the base film and the coating, improving the bonding strength between the base film and the coating, thereby effectively improving the tensile strength and other mechanical properties of the composite current collector and increasing the service life of the composite current collector and the battery.
[0008] The bimetallic strip mentioned above is a composite material composed of two or more metals or other materials with suitable properties. The bimetallic strip is also called a thermal bimetallic strip or a bimetallic piece. Due to the different thermal expansion coefficients of each component layer, when the temperature changes, the deformation of the active layer is greater than the deformation of the passive layer, so that the entire bimetallic strip will bend toward the passive layer, and the curvature of the composite material changes to produce deformation. In the memory metal sheet, the memory metal refers to a special metal material that can restore its original macroscopic shape in another temperature range after plastic deformation in a certain temperature range. The bimetallic strip and the memory metal sheet used in the present invention are both thinner sheets, so that there is a more obvious deformation, and it can achieve obvious deformation at a certain high temperature when using a small amount of bimetal or memory metal, and timely and effectively form multi-point and large-area rapid disconnection on the composite current collector, effectively improving the thermal safety performance of the composite current collector, thereby improving the thermal safety performance of the battery.
[0009] In addition, it should be noted that the main function of the oxide coating is to enhance the bonding strength between the base film and the conductive layer. At the same time, the oxide coating is generally a brittle ceramic material. When the battery is subjected to external forces such as puncture and impact, it can break and tear, thereby giving the composite current collector a certain ability to suppress thermal runaway, and the oxide coating can also play a certain role in resisting electrolyte corrosion. Therefore, the oxide coating and the conductive layer are both an indispensable part of the composite current collector and play an important role in the relevant properties of the composite current collector.
[0010] Preferably, the mass proportion of the thermal deformation sheet in the base film is 10-20%. If the mass proportion of the thermal deformation sheet in the base film is too small, it will not produce sufficient and obvious thermal deformation at a certain high temperature, and the tension provided to the conductive metal layer will be small, and thus it will not be able to effectively drive the brittle oxide coating to undergo continuous fracture, resulting in fewer short-circuit sites and fewer areas, which will lead to limited improvement in the thermal safety performance of the composite current collector. If the mass proportion of the thermal deformation sheet in the base film is too small, the metal network formed in the base film will be small, and the conductivity and tensile strength of the composite current collector will also decrease, resulting in a decrease in the performance of the composite current collector, and the safety performance and service life of the battery cannot be effectively improved. If the mass proportion of the thermal deformation sheet in the base film is too large, the metal content in the base film will be high, which will cause the performance of the polymer material to decrease, resulting in a decrease in the hardness, chemical resistance and thermal stability of the polymer material, which is not conducive to the performance of the base film, deteriorating the service life of the base film, and affecting the safety performance and service life of the battery. Moreover, if the mass of the thermally deformable sheet in the base film accounts for too large a proportion, the tension provided to the conductive metal layer is relatively large, and continuous microcracks are formed on the composite current collector before a certain high temperature is reached, resulting in large-scale circuit breakage too early, causing the battery to fail quickly. This is not conducive to the battery utilization rate and is also not conducive to actual use.
[0011] Preferably, in the base film, the thermal deformation sheet is completely wrapped by the polymer material. The thermal deformation sheet is completely wrapped by the polymer material, which, on the one hand, makes the connection between the thermal deformation sheet and the polymer material tighter, and the thermal deformation sheet forms a more uniform and stable conductive network inside the base film, which is more conducive to the mechanical properties and conductive properties of the composite current collector. On the other hand, the deformation of such a strongly wrapped thermal deformation sheet at high temperature is more obvious, which is more conducive to improving the thermal safety performance of the composite current collector.
[0012] Preferably, the bimetallic sheet includes at least one of Ni-Fe alloy, Fe-Co alloy, and Cu-Fe alloy; the memory metal sheet includes at least one of TiNi alloy, CuZn alloy, CuZnAl alloy, and CuAlNi alloy. The composite current collector formed by the above-mentioned bimetallic sheet and memory metal sheet can achieve relatively fast multi-site and large-area rapid circuit breaking when the battery is at a certain high temperature, effectively improving the thermal safety performance of the composite current collector and the battery.
[0013] Preferably, the thickness of the base film is 4.5-6 μm, and the thickness of the thermal deformation sheet is 0.3-1.5 μm. Controlling the thickness of the base film and the thickness of the thermal deformation sheet within the above range can ensure that the thermal deformation sheet has enough space for thermal deformation, and at the same time, can ensure that the thermal deformation sheet can be well combined with the base film without obvious stratification, thereby improving the overall strength of the composite current collector.
[0014] Preferably, the thermal deformation sheet includes at least one of a strip-shaped thermal deformation sheet and a mesh-shaped thermal deformation sheet; in the mesh-shaped thermal deformation sheet, the mesh shape includes at least one of a triangle, a rhombus, a square, a hexagon, a rectangle, and a circle. The strip-shaped and mesh-shaped thermal deformation sheets are more conducive to the thermal deformation sheet being able to quickly and significantly deform under a certain high temperature, without having to overcome too much of its own tension to undergo thermal deformation, and maximizing the use of thermal deformation. Using a smaller amount of thermal deformation sheets can achieve more effective deformation and improve the safety performance of the composite current collector. Such a strip-shaped and mesh-shaped structure enables more and more uniform metal conductive networks to be formed inside the base film when a certain mass of thermal deformation sheets is introduced into the base film, which is more conducive to improving the overall conductivity and tensile strength of the composite current collector.
[0015] Preferably, the thickness of the oxide coating is 50 to 55 nm, and the thickness of the conductive layer is 0.5 to 2 μm. The oxide coating cannot be too thick. Too thick will affect the thermal deformation metal network formed inside the base film, and the tension provided to the conductive layer will be reduced when it is deformed at a certain high temperature, thereby affecting the short-circuit effect of the oxide coating at high temperatures. If the thickness of the conductive layer (such as the metal layer) is too small, it will affect the conductive properties of the composite current collector. If the conductive layer is too thick, the tension provided to the conductive layer by the thermal deformation metal network at a certain high temperature will be relatively insufficient, which will also cause the tension provided to the conductive layer to become smaller, thereby affecting the short-circuit effect of the oxide coating at high temperatures. Therefore, both the oxide coating and the conductive layer need to be kept within a certain thickness range in order to take into account the overall conductivity, tensile properties, and short-circuit performance at high temperatures of the composite current collector.
[0016] Preferably, in the oxide coating, the oxide includes at least one of aluminum oxide and silicon oxide; and in the conductive layer, the conductive material includes at least one of aluminum and copper.
[0017] Preferably, in the above-mentioned composite current collector, when in the base film, the thermally deformable sheet is completely wrapped by the polymer material, the preparation method of the base film includes the following steps: a1. placing the thermally deformable sheet in the mold, and then placing the molten polymer material into the mold, so that the thermally deformable sheet is completely wrapped by the molten polymer material; a2. extruding it into a film through the mold, and then stretching it longitudinally and transversely, after integrated heat setting, cooling and cutting to obtain the base film.
[0018] Preferably, in the above-mentioned composite current collector, when in the base film, the thermally deformable sheet is combined with the polymer material in an internal and external interlaced manner, the preparation method of the base film comprises the following steps: b1. placing the thermally deformable sheet in a wave-like manner in a mold, and then placing the molten polymer material in the mold, so that the thermally deformable sheet is combined with the molten polymer material in an internal and external interlaced manner; b2. extruding it into a film through a mold, and then stretching it longitudinally and transversely, after integrated heat setting, cooling and cutting to obtain a base film;
[0019] The above-mentioned preparation methods are all prepared by mixing or combining the thermally deformable sheet with the molten polymer material and then thermally shaping the sheet as a whole. This allows the thermally deformable sheet to be tightly connected to the polymer material, and the thermally deformable sheet can form a uniform metal network inside or outside the base film, thereby effectively improving the safety performance, conductivity, tensile performance and other aspects of the composite current collector, thereby effectively improving the safety performance and service life of the battery.
[0020] Preferably, in a1, during the process of placing the thermal deformation sheets in the mold, the thermal deformation sheets are placed at certain intervals.
[0021] Preferably, in a2, b2, and c2, the preheating roller temperature of the longitudinal stretching process is set at 60-80°C, the slow pulling roller temperature is 80-85°C, the fast pulling roller temperature is 28-35°C, the cooling roller temperature is 30-50°C, and the longitudinal stretching ratio is set to 3-3.5 times; the preheating roller temperature of the transverse stretching process is set at 80-100°C, the slow pulling roller temperature is 100-105°C, and the longitudinal stretching ratio is set to 3-3.5 times.
[0022] Preferably, in a2, b2, c2, the heat setting temperature is 190-210°C.
[0023] Preferably, in the process of preparing the composite current collector, an oxide layer and a conductive layer are sequentially formed on the base film in at least one of the following ways: magnetron sputtering and vacuum coating.
[0024] In summary, the present invention introduces a thermally deformable sheet (including at least one of a bimetallic sheet and a memory metal sheet) in the process of preparing the base film, so that the thermally deformable sheet forms a good metal network inside or inside the base film. The metal network can be deformed at a certain high temperature, so that multi-point and large-area rapid disconnection can be achieved on the composite current collector, and the metal network can also improve the conductivity and mechanical properties of the composite current collector, such as tensile strength, thereby effectively improving the thermal safety, conductivity and tensile strength of the composite current collector, thereby optimizing the thermal safety performance and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the base film preparation process in Example 5. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0027] Example 1
[0028] The composite current collector of this embodiment is prepared according to the following steps:
[0029] Step 1: First, in the mold, a strip memory metal sheet with a thickness of 1 μm is placed along the film extrusion direction and arranged in the film width direction (with an interval of 1 cm), that is, while the polymer material is extruded, the strip memory metal sheet is continuously fed and wired, and output from the mold together; and the polymer material (base film raw material) is dried to remove moisture, and then hot-melted at high temperature, and then poured into the mold, so that the polymer material completely wraps the memory metal sheet; the memory metal sheet is TiNi alloy; the polymer material is polyethylene terephthalate (PET); and the feeding amount of the memory metal sheet and the polymer material is calculated based on the mass proportion of the memory metal sheet in the base film being 15%;
[0030] Step 2: Form the initial shape of the film through die extrusion, then stretch longitudinally and transversely, after heat setting, cooling, slitting, thickness measurement, corona treatment, etc., to obtain a base film, and the thickness of the base film is 6 μm; wherein the longitudinal stretching preheating roller is set to 70°C, the slow pull roller temperature is 80°C, the fast pull roller temperature is 30°C, the cooling roller temperature is 40°C, and the longitudinal stretch ratio is set to 3 times; the transverse stretching preheating roller temperature is set to 80°C, the slow pull roller temperature is 100°C, and the transverse stretch ratio is set to 3 times; the heat setting temperature is 200°C, the time is 5 seconds, and the heat setting is cooled to 50°C after setting;
[0031] Step 3: The obtained base film is coated with an alumina coating and an aluminum layer in sequence; wherein, the film-releasing end is at 120N, the winding end is at 100N, and the winding trolley enters the evaporation chamber and is vacuumed to 5*10 -3 Pa, turn on the winding trolley, control the speed at 280-300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300-350mm / min, turn on the oxygen intake, and control the vacuum degree at 5*10 -2 Pa, so that an aluminum oxide coating is formed on the surface of the base film, and the thickness of the aluminum oxide coating is controlled to be 55nm; then the vacuum is broken, and an aluminum layer is continuously deposited in the same manner, and the thickness of the aluminum layer is 1μm.
[0032] It should be noted that after the longitudinal stretching and transverse stretching in step 2, the strip-shaped memory metal sheet may be broken into multiple dotted line-shaped segment-shaped memory metal sheets in the longitudinal direction according to the different ductility of the metal, or it may be stretched and thinned, and the spacing in the transverse direction will be greater than the preset spacing. The grid-shaped memory metal sheet is in a folded or bent state when it is extruded with the polymer material, and is unfolded into a mesh after stretching. Partial breaking and thinning are allowed to occur during the stretching process. The shape change of the memory metal sheet during the base film molding process does not affect its ability to achieve multi-site, large-area rapid disconnection when the battery temperature changes.
[0033] Example 2
[0034] In the process of preparing the composite current collector in this embodiment, the difference from that in Embodiment 1 is that the thermal deformation sheet is a mesh-shaped memory metal sheet, and the mesh holes are triangular. The rest is the same as in Embodiment 1.
[0035] Example 3
[0036] In the process of preparing the composite current collector in this embodiment, the difference from that in Embodiment 1 is that the thermal deformation sheet is a mesh-shaped memory metal sheet, and the mesh holes are rhombus-shaped. The rest is the same as that in Embodiment 1.
[0037] Example 4
[0038] In the process of preparing the composite current collector in this embodiment, the difference from the embodiment 1 is that the thermal deformation sheet is a mesh memory metal sheet, the mesh holes are rhombus-shaped, and the thickness of the mesh memory metal sheet is 0.5 μm. The rest is the same as the embodiment 1.
[0039] Example 5
[0040] In the process of preparing the composite current collector in this embodiment, the difference from that in embodiment 4 is that the specific operation in step 1 is to place the memory metal sheet in the mold in a wave-like manner, and then pour in the polymer material that has been melted by high-temperature heat melting, so that the memory metal sheet is combined with the molten polymer material in an internal and external interlaced manner. The rest is the same as in embodiment 4.
[0041] Example 6
[0042] In the process of preparing the composite current collector in this embodiment, the difference from that in embodiment 1 is that the strip-shaped memory metal sheet in step 1 is replaced by a strip-shaped bimetallic sheet, and the specific bimetallic sheet is a Ni-Fe alloy. The rest is the same as in embodiment 1.
[0043] Example 7
[0044] The process of preparing the composite current collector in this embodiment is different from that in Embodiment 1 in that in step 1, the amount of the memory metal sheet and the polymer material is calculated based on the mass proportion of the memory metal sheet in the base film being 8%. The rest is the same as in Embodiment 1.
[0045] Example 8
[0046] The process of preparing the composite current collector in this embodiment is different from that in Embodiment 1 in that in step 1, the amount of the memory metal sheet and the polymer material is calculated based on the mass proportion of the memory metal sheet in the base film being 23%. The rest is the same as in Embodiment 1.
[0047] Example 9
[0048] In the process of preparing the composite current collector in this embodiment, the difference from that in Embodiment 1 is that the thickness of the strip-shaped memory metal sheet in step 1 is adjusted to 0.2 μm. The rest is the same as that in Embodiment 1.
[0049] Example 10
[0050] In the process of preparing the composite current collector in this embodiment, the difference from that in Embodiment 1 is that the thickness of the strip-shaped memory metal sheet in step 1 is adjusted to 1.8 μm. The rest is the same as that in Embodiment 1.
[0051] Embodiment 11
[0052] The process of preparing the composite current collector in this embodiment is different from that in Embodiment 1 in that in step 3, in the process of forming the aluminum oxide coating, the relevant process parameters are controlled so that the thickness of the aluminum oxide coating finally formed is 60 nm. The rest is the same as in Embodiment 1.
[0053] Example 12
[0054] The process of preparing the composite current collector in this embodiment is different from that in Embodiment 1 in that in step 3, in the process of forming the aluminum layer (conductive layer), the relevant process parameters are controlled so that the thickness of the aluminum layer finally formed is 0.3 μm. The rest is the same as in Embodiment 1.
[0055] Embodiment 13
[0056] The process of preparing the composite current collector in this embodiment is different from that in Embodiment 1 in that in step 3, in the process of forming the aluminum layer (conductive layer), the relevant process parameters are controlled so that the thickness of the aluminum layer finally formed is 2.3 μm. The rest is the same as in Embodiment 1.
[0057] Comparative Example 1
[0058] In the process of preparing the composite current collector in this comparative example, the difference from Example 1 is that no memory metal sheet is added in step 1, and the polymer material in a molten state after high temperature heat melting is directly poured in to form a base film. The rest is the same as Example 1.
[0059] Test Case
[0060] 1. Experimental Construction Method
[0061] The composite current collectors prepared in all the above embodiments and comparative examples were tested for surface square resistance, tensile strength MD, tensile strength TD, and thermal stability. The specific test methods are as follows:
[0062] Surface square resistance: The square resistance is measured using a four-probe resistivity tester. The number of square resistance tests is determined based on the lateral width of the product, with one point tested every 100mm. Other requirements are tested according to the method specified in GB / T 22638.6-2016.
[0063] Tensile strength: The room temperature tensile strength and elongation at break of the composite aluminum foil were measured using an electronic universal material testing machine. The test conditions were a gauge length of 10 mm, a tensile speed of 100 mm / nin, and a width of 15 mm. Other requirements were measured according to the method specified in GB / T1040.3-2006.
[0064] Thermal stability: The surface resistance of the composite current collector was tested before heating and at 60°C, 80°C, 100°C, 120°C, 140°C and 160°C. The thermal stability of the composite current collector was evaluated based on the change in surface resistance.
[0065] 2. Experimental results
[0066] The test results of surface square resistance, tensile strength MD, tensile strength TD and thickness of the composite current collectors prepared in all the above embodiments and comparative examples are shown in Tables 1 and 2.
[0067] Table 1 Test results of surface square resistance, tensile strength MD, tensile strength TD, of composite current collector in the embodiment and comparative example
[0068]
[0069]
[0070] Table 2 Test results of thermal stability of composite current collectors in Examples and Comparative Examples
[0071]
[0072] It can be seen from Table 1 and Table 2 that the addition of memory metal sheets or bimetal sheets improves the tensile strength of composite current collectors such as composite aluminum current collectors. After high-temperature treatment, the thermal extension deformation of memory metal and bimetal sheets reduces the tensile strength while increasing the square resistance. When a certain temperature is reached, the deformation increases, thereby driving the middle oxide coating (ceramic base layer) with greater brittleness to undergo continuous microcrack fracture, achieving multi-point, large-area rapid circuit breaking, and further improving the thermal safety of the composite current collector. For details, refer to Examples 1 to 13.
[0073] No memory metal sheet is added to the composite current collector in Comparative Example 1, resulting in a decrease in the tensile strength of the composite current collector before heat treatment. At the same time, the tensile strength of the composite current collector after heat treatment is also high, and the heating resistance is also low, which indicates that there is no memory metal sheet, that is, the thermal deformation performance of the memory metal sheet is lost, resulting in the oxide coating (ceramic base layer) with greater brittleness in the middle of the composite current collector not being broken by continuous microcracks under high temperature conditions, which on the one hand keeps its tensile strength high, and more importantly, it cannot be broken at multiple points and over a large area quickly, so that the high-temperature surface resistance of the composite current collector is still low, and the thermal safety of the composite current collector cannot be effectively improved.
[0074] Further observation of Examples 1 to 3 shows that when the mesh shape of the memory metal sheet is changed, the tensile strength of the composite current collector after heat treatment is lower, and the heating surface resistance is also larger, which indicates that when the mesh shape of the memory metal sheet is changed, the prepared composite current collector still has higher thermal safety. And compared with the mesh shape of the triangular, strip-shaped memory metal sheet and the mesh shape of the diamond-shaped mesh memory metal sheet, the corresponding composite current collector has better thermal safety performance.
[0075] Comparing Examples 4 and 5, when the placement of the memory metal sheet in the polymer material is changed, the thermal safety performance of the composite current collector will be affected to a certain extent. When the memory metal sheet is completely wrapped by the polymer material in Example 4, the thermal deformation performance of the memory metal sheet in the polymer material is most obvious. Therefore, the corresponding composite current collector has the lowest tensile strength after heat treatment, the highest high-temperature surface resistance, and the best thermal safety performance.
[0076] By comparing Examples 1 and 6, it can be found that when the memory metal sheet is replaced with a bimetallic sheet that also has thermal deformation performance, the composite current collector still has good thermal safety performance.
[0077] Comparing Example 1 with Examples 7-8, the proportion of the memory metal sheet in the base film in Examples 7 and 8 is too little and too much, respectively. Both too little and too much will affect the thermal stability of the composite current collector. Therefore, further controlling the memory metal sheet within a specific range is more conducive to the thermal safety performance of the composite current collector.
[0078] Comparing Example 1 with Examples 9 to 10, the memory metal sheets in Examples 9 and 10 are thinner and thicker, respectively. Because the composite current collector is a whole, a thinner or thicker memory metal sheet will have a certain impact on the relevant properties of the composite current collector. Therefore, further limiting the thickness of the memory metal sheet within a certain numerical range is more beneficial to the thermal safety performance and other aspects of the composite current collector.
[0079] Comparing Example 1 with Examples 11 to 13, the oxide coating in Example 11 is thicker, and the conductive layers in Examples 12 and 13 are thinner and thicker, respectively, which results in a decrease in the thermal safety performance of the composite current collectors in Examples 11 to 13. This indicates that the oxide coating and the conductive layer in the composite current collector will also have a certain impact on the performance of the composite current collector, and limiting the thickness of the oxide coating and the conductive layer within a certain range is more conducive to the thermal safety performance of the composite current collector.
[0080] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A composite current collector, characterized in that: It includes a base film, an oxide coating, and a conductive layer in sequence; The base film includes a polymer material and a thermally deformable sheet; In the base film, the thermally deformable sheet is completely wrapped by the polymer material; Or in the base film, the thermally deformable sheet is combined with the polymer material in an internal and external interlaced manner; The polymer material includes at least one of polypropylene, polyethylene terephthalate, and polyimide; The thermal deformation sheet includes at least one of a bimetal sheet and a memory metal sheet.
2. The composite current collector according to claim 1, characterized in that: The mass proportion of the thermal deformation sheet in the base film is 10-20%.
3. The composite current collector according to claim 1, characterized in that: In the base film, the thermally deformable sheet is completely wrapped by the polymer material.
4. The composite current collector according to claim 1, characterized in that: The bimetallic sheet comprises at least one of a Ni-Fe alloy, a Fe-Co alloy, and a Cu-Fe alloy; The memory metal sheet includes at least one of TiNi alloy, CuZn alloy, CuZnAl alloy and CuAlNi alloy.
5. The composite current collector according to claim 1, characterized in that: The base film has a thickness of 4.5 to 6 μm, and the thermal deformation sheet has a thickness of 0.3 to 1.5 μm.
6. The composite current collector according to claim 1, characterized in that: The thermal deformation sheet includes at least one of a strip-shaped thermal deformation sheet and a mesh-shaped thermal deformation sheet; in the mesh-shaped thermal deformation sheet, the mesh shape includes at least one of a triangle, a rhombus, a square, a hexagon, a rectangle, and a circle.
7. The composite current collector according to claim 1, characterized in that: The thickness of the oxide coating is 50-55 nm, and the thickness of the conductive layer is 0.5-2 μm.
8. The composite current collector according to claim 1, characterized in that: In the oxide coating, the oxide includes at least one of aluminum oxide and silicon oxide; In the conductive layer, the conductive material includes at least one of aluminum and copper.
9. The composite current collector according to claim 1, characterized in that: When the thermally deformable sheet is completely wrapped by the polymer material in the base film, the preparation method of the base film comprises the following steps: a1. placing the heat-deformable sheet in the mold, and then placing the molten polymer material into the mold, so that the heat-deformable sheet is completely wrapped by the molten polymer material; a2. Extruding into a film through the die, followed by longitudinal stretching and transverse stretching, integrated heat setting, cooling, and slitting to obtain the base film.
10. The composite current collector according to claim 1, characterized in that: When the thermally deformable sheet is combined with the polymer material in an internal and external interlaced manner in the base film, the preparation method of the base film includes the following steps: b1. placing the heat-deformable sheet in a wave-like manner in the mold, and then placing the molten polymer material in the mold, so that the heat-deformable sheet is combined with the molten polymer material in an interlaced manner; b2. Extruding into a film through the die, followed by longitudinal stretching and transverse stretching, integrated heat setting, cooling, and slitting to obtain the base film.